The Mediating Role of Perceived Stress and Student Engagement for Student Teachers’ Intention to Drop Out of University in Germany: An Analysis Using the Study Demands–Resources Model Under Pandemic and Post-Pandemic Conditions - Edgar Hahn; Dina Kuhlee; Julia Zimmermann; Juan Serrano-Sánchez (Education Sciences)
This article examines the interplay between study demands, institutional resources, and individual resources, specifically resilience, with the perceived stress, study engagement, and dropout intentions of student teachers using the Study Demands–Resources model. The aim is to describe the relevance of these variables in relation to student teachers’ intention to drop out of their studies as an indicator of student success. Further, we aim to explore whether the correlation structures can also be confirmed under different conditions, particularly in the context of the COVID-19 pandemic. To answer these questions, data collected under pandemic study conditions (NLA1 = 510) and post-pandemic study conditions (NLA2 = 433) are used and analysed by SEM. The results show that the Study Demands–Resources model is applicable in the two different contexts based on its validation in both study contexts. In line with the model, in both contexts, perceived stress and student engagement were significantly related to student teachers’ dropout intentions. Furthermore, study demands and resilience influenced perceived stress, which in turn affected dropout intentions, whereas institutional resources were associated with dropout intentions via student engagement. This article contextualises the findings within the existing research landscape. Based on the results, theoretical implications are discussed and approaches to reduce perceived stress in a sustainable manner to support student teachers and their academic success are described.